Plasma p-tau217 and tau-PET predict future cognitive decline among cognitively unimpaired individuals : implications for clinical trials - Ossenkoppele, Rik; Salvadó, Gemma; Janelidze, Shorena; Pichet Binette, Alexa; Bali, Divya; Karlsson, Linda ; 0000-0002-0630-772X; Palmqvist, Sebastian ; 0000-0002-9267-1930; Mattsson-Carlgren, Niklas ; 0000-0002-8885-7724; Stomrud, Erik ; 0000-0002-0841-5580; Therriault, Joseph; Rahmouni, Nesrine; Rosa-Neto, Pedro; et al. (Nature Aging, 2025)
Plasma p-tau217 and tau positron emission tomography (PET) are strong prognostic biomarkers in Alzheimer’s disease (AD), but their relative performance in predicting future cognitive decline among cognitively unimpaired (CU) individuals is unclear. In a head-to-head comparison study including nine cohorts and 1,474 individuals, we show that plasma p-tau217 and medial temporal lobe tau-PET signal display similar associations with cognitive decline on a global cognitive composite test (R2PET = 0.34 versus R2plasma = 0.33, Pdifference = 0.653) and with progression to mild cognitive impairment (hazard ratio (HR)PET = 1.61 (1.48–1.76) versus HRplasma = 1.57 (1.43–1.72), Pdifference = 0.322). Combined plasma and PET models were superior to the single-biomarker models (R2 = 0.35, P < 0.01). Sequential selection using plasma phosphorylated tau at threonine 217 (p-tau217) and then tau-PET reduced the number of participants required for a clinical trial by 94%, compared to a 76% reduction when using plasma p-tau217 alone. Thus, plasma p-tau217 and tau-PET showed similar performance for predicting future cognitive decline in CU individuals, and their sequential use enhances screening efficiency for preclinical AD trials.